Influence of socio-economic indicators and territorial networks at the spatiotemporal spread dynamics of Covid-19 in Brazil - Miguel da Guia Albuquerque; Jefferson Rodrigues dos Santos; Angelita Fialho Silveira; Dardo Lorenzo Bornia Junior; Rozele Borges Nunes; Tiago Borges Ribeiro Gandra; André Luis Corrêa da Silva; Gustavo Borba de Miranda; Alessandra Ruiz Trevisol (Sociedade & Natureza)
This work aims to provide an overview of the territorial evolution of COVID-19 (SARS-CoV-2) in Brazil using socio-demographic variables, for the time span between February 26, 2020 until January 24, 2021. Socio-demographic indicators, basic sanitation infrastructure data, and epidemiological bulletins were integrated using Principal Components Analysis (PCA) to develop a social vulnerability index (SVI), to estimate the degree of exposure risk of the Brazilian population to COVID-19. The results indicate that the majority of confirmed cases were reported from the main Brazilian capitals, linked to well-developed port and airport modes. In terms of deaths, the states of São Paulo, Rio de Janeiro, Ceará and Pernambuco were at the top of the ranking. On the contrary, there were some states of the mid-west (Mato Grosso do Sul) and the north (Acre, Amapá, Roraima, Rondônia and Tocantins), that recorded low mortality indexes. The SVI reveals that the states of the north and north-east are the most vulnerable. Regarding the metropolitan areas, it was observed that the main capitals of the north and north-east, with the exception of Salvador, present significantly more critical numbers in terms of dissemination and deaths by COVID-19 than the capitals of the south-southeast, where the SVI is lower. The comparative exception was Santa Catarina state metropolitan areas. Finally, as the virus does not strike everyone in the same way, one of the great challenges is to search for solutions to cope with COVID-19 in the face of very unequal realities. Thus, a reflection on the strategies adopted by the Brazilian government is relevant, while considering the continental dimensions and the diversity of the Brazilian regions, to obtain a better analysis of the more vulnerable populations and social groups.